Contact-induced grammar formation: A model from a study on Hiberno-English - Shimada, Tamami (Frontiers in Communication, 2022)
This paper examines how certain characteristic grammatical forms in Hiberno-English (HE) are the result of a dynamic process of language formation guided by language contact. A first language contact between Irish and English gives rise to the grammar formation of HE, and a second contact between HE and other varieties of English, presumably over the past 50 years or so, has pruned HE to fit the speakers’ awareness towards the standard norm. Examinations into expressions of tense/aspect and information structure in HE lead to the suggestion of grammatical oppositions being inherited from Irish and the resilience of this inheritance in present-day HE. Taking three salient characteristics of HE, the "be after perfect," the "do be" habitual, and the "’tis….. construction" as windows into its underlying properties, the paper surveys earlier forms in the rise of HE and describes some facets of contemporary HE. One of the central issues in the examination is Irish-language traits and their realization in HE morphosyntax. The paper concludes by proposing an integrated perspective across the characteristics and a model to capture the grammar formation of HE, which can be applied to find similarities and contrasts with other language-contact phenomena.